Kegiatan Perpustakaan Keliling di Kantor Perpustakaan Arsip Dokumentasi Kabupaten Pesisir Selatan Dalam Meningkatkan Minat Baca Masyarakat Tarusan - Rahayu, Mugi; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper aims to: (1) to describe the implementation of a mobile library Library Archives Office Documentation in the South Coastal District to increase reading in Tarusan. (2) Describe any obstacles encountered Library bookmobile Office Documentation Archive South Coastal District in the implementation of activities in an effort to increase reading in Tarusan. Data collection methods were observation and interview. Observation is a way of collecting data by direct observation area to Tarusan with librarians. Data collection interview by talking directly with the public face to face or Tarusan and librarians who can provide information. Keywords: activities; improve reading Â